A Vulnerable Justice: Finality of Civil Judgments in China - Liu, Nanping (Columbia Journal of Asian Law, 1999)
This Article challenges the finality of a civil judgement in the People’s Republic of China, i.e., the so-called system in which a decision by the court of second instance is final (liangshen zhongshen zhi) (the “regular trial system”). There is a widespread conception among legal scholars, judges and lawyers that judicial finality can be obtained in China, because under the regular trial system litigants have only two chances to have their disputes heard by the court. However, the opposite view, once held by this author, is that, from a Western perspective, finality simply does not exist in China. A Chinese court may have endless chances, without any time limit, to decide a case under the Procedure of Trial Supervision (shenpan ]iandu chengxu) (“the Supervision Procedure” or “supervising system”). The analysis this author offers in this Article demonstrates that, contrary to the popular conception in Mainland China or to the view made from a Western perspective, an extreme conclusion either way on the issue of finality is superficial. As a matter of fact, “judicial finality” itself is a complicated or even misleading term under the Chinese legal system. In determining the meaning of finality, one has to take into account the actual operation of the entire Chinese system instead of perceiving it narrowly based on the written law. Most importantly, particular attention should be paid to those factors affecting the implementation of law, such as Chinese legal culture and the political structure. Accordingly, this Article offers two alternative but decisive rules on the finality issue. These rules should be considered when a Chinese civil judgement is to be recognized and enforced in a foreign jurisdiction.